Construction of a composite sow inded and study of its effects due to sire, parity and season in pigs - Gini Varghese (Department of Agricultural Statistics, College of Horticulture, 1995)
An investigation was done for the constructions of composite sow index based on the data collected from sow cards of pigs maintained at the University Pig Breeding Farm, Mannuthy, with the additional objectives of studying the effect of sire, parity and season on this index and also to suggest for culling the uneconomic animals based on this index.